28.3% Efficient III–V Tandem Solar Cells Fabricated Using a Triple‐Chamber Hydride Vapor Phase Epitaxy System. Issue 4 (19th December 2021) - Shoji, Yasushi; Oshima, Ryuji; Makita, Kikuo; Ubukata, Akinori; Sugaya, Takeyoshi
Abstract : Hydride vapor phase epitaxy (HVPE) is a III–V device fabrication technology that has received attention owing to its low production costs. The properties of passivation layers used to reduce surface and interface recombination losses in III–V materials considerably contribute to the performance of various devices. Herein, solar cells based on AlInGaP back‐surface field (BSF) layers grown via HVPE using aluminum trichloride as the group‐III precursor for Al deposition are presented. Although high‐concentration Si contamination occurs in Al‐containing layers grown using HVPE, AlInGaP with p‐type conductivity can be grown by doping with high‐concentration Zn. For InGaP single‐junction solar cells, the short‐circuit current density and open‐circuit voltage are improved by introducing the AlInGaP BSF layer. Consequently, the InGaP single‐junction solar cells measured under air mass 1.5 global solar spectrum illumination achieve a conversion efficiency of 17.1%. Furthermore, the progress in the development of tandem solar cells grown using HVPE is reported. By improving the performance of the InGaP top cells, InGaP/GaAs tandem cells are fabricated with a new record efficiency of 28.3% using the triple‐chamber HVPE system. Abstract : Hydride vapor phase epitaxy (HPVE) is a promising growth technique for reducing the fabrication cost of III–V devices. The improvement in the solar cell performance by introducing AlInGaP back‐surface field layers is reported. Consequently, 28.3% efficient InGaP/GaAs tandem solar cells, the highest conversion efficiency reported in cells grown via HPVE, is achieved.